Lattice Dynamics, Phonon Chirality, and Spin–Phonon Coupling in 2D Itinerant Ferromagnet Fe3GeTe2. (25th September 2019) - Du, Luojun; Tang, Jian; Zhao, Yanchong; Li, Xiaomei; Yang, Rong; Hu, Xuerong; Bai, Xueyin; Wang, Xiao; Watanabe, Kenji; Taniguchi, Takashi; Shi, Dongxia; Yu, Guoqiang; et al.
Abstract: Fe3 GeTe2 has emerged as one of the most fascinating van der Waals crystals due to its 2D itinerant ferromagnetism, topological nodal lines, and Kondo lattice behavior. However, lattice dynamics, chirality of phonons, and spin–phonon coupling in this material, which set the foundation for these exotic phenomena, have remained unexplored. Here, the first experimental investigation of the phonons and mutual interactions between spin and lattice degrees of freedom in few‐layer Fe3 GeTe2 is reported. The results elucidate three prominent Raman modes at room temperature: two A1g (Γ) and one E2g (Γ) phonons. The doubly degenerate E2g (Γ) mode reverses the helicity of incident photons, indicating the pseudoangular momentum and chirality. Through analysis of temperature‐dependent phonon energies and lifetimes, which strongly diverge from the anharmonic model below Curie temperature, the spin–phonon coupling in Fe3 GeTe2 is determined. Such interaction between lattice oscillations and spin significantly enhances the Raman susceptibility, allowing to observe two additional Raman modes at the cryogenic temperature range. In addition, laser radiation‐induced degradation of Fe3 GeTe2 in ambient conditions and the corresponding Raman fingerprint is revealed. The results provide the first experimental analysis of phonons in this novel 2D itinerant ferromagnet and their applicability for further fundamental studies and application development. Abstract : Via systematic linear polarization‐ and helicity‐resolved Raman measurements, the fingerprint and chirality of phonons in 2D itinerant ferromagnet Fe3 GeTe2 are elucidated for the first time. Importantly, the spin–phonon coupling is determined through analysis of temperature‐dependent phonon energies and lifetimes. Such spin–phonon coupling significantly enhances the Raman susceptibility. Finally, the Raman fingerprints associated with the degradation of Fe3 GeTe2 are uncovered.